Cardioprotective Effects of Qishenyiqi Mediated by Angiotensin II Type 1 Receptor Blockade and Enhancing Angiotensin-Converting Enzyme 2. (13th November 2012) - Wang, Yong; Li, Chun; Ouyang, Yulin; Yu, Junda; Guo, Shuzhen; Liu, Zhongyang; Li, Dong; Han, Jing; Wang, Wei
Abstract : The aim of this paper was to investigate whether the effects of QSYQ on CHD are associated with the renin-angiotensin-aldosterone system (RAAS). The formula groups were lavaged with QSYQ, using fosinopril sodium as a control. The level of RAAS components in the myocardial tissue was measured, respectively. The results showed that both QSYQ and fosinopril sodium can improve the ejection fraction in CHD and that QSYQ decreases the left ventricular end-systolic diameter and left ventricular end-diastolic diameter, while fosinopril sodium has no effects on these parameters. Fosinopril sodium, as an ACE inhibitor, downregulated ACE expression and eventually reduced the tissue AngII concentration but had no effect on ACE2. Moreover, it had no effect on renin or AT2, while QSYQ significantly decreased the level of renin and expression of AngII in myocardial tissue. The results also revealed that QSYQ can act on both AT1 and AT2, thus, blocking the effect of AngII and increasing the level of ACE2. It also downregulated the levels of TGF-β and MMP-9, but it had no effect on ACE. This study showed that the ameliorative effects of QSYQ on CHD in rats had multiple targets associated with the inhibition of RAAS, thus, producing cardioprotective therapy effects.